Application of aloe peel biological carbon material in preparation of lithium-sulfur battery

By using aloe vera biocarbon material to prepare KOH@AVP/S positive electrode material and Co@AVP separator modified material, the problems of lithium sulfur batteries in cyclic stability and rate performance are solved, and high energy density and excellent electrochemical performance are achieved.

CN119864421AActive Publication Date: 2025-04-22HUAQIAO UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510061930.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-22
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

Lithium-sulfur batteries have problems in cycle stability, rate performance, Coulomb efficiency and active substance loss, which limits their commercialization process.

Method used

Aloe vera biocarbon material is used to prepare KOH@AVP/S positive electrode material and Co@AVP diaphragm modified material. Through high-temperature annealing, KOH etching, sulfur fusion reaction and hydrothermal reaction, materials with high specific surface area and catalytic activity are formed.

Benefits of technology

The excellent cycle stability and rate performance of lithium-sulfur batteries are achieved, and the energy density and electrochemical performance of the battery are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864421A_ABST
    Figure CN119864421A_ABST
Patent Text Reader

Abstract

The invention discloses application of an aloe peel biological carbon material in preparation of a lithium-sulfur battery, the aloe peel biological carbon material is used as a raw material for preparing a positive electrode and a diaphragm of the lithium-sulfur battery, the raw material of the positive electrode comprises a KOH (at) AVP / S positive electrode material, and the raw material of the diaphragm comprises a Co (at) AVP diaphragm modified material. According to the preparation method, an aloe peel biomass carbon material is adopted as a precursor, a positive sulfur host KOH (at) AVP / S positive electrode material with a high specific surface area is obtained through KOH etching, meanwhile, Co metal nanoparticles are introduced through a simple hydrothermal reaction, and a Co (at) AVP diaphragm modified material capable of being used for modifying a diaphragm is prepared. The two materials are simultaneously applied to the lithium-sulfur battery and can play a synergistic role.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium-sulfur battery materials, and particularly relates to use of aloe vera peel biocarbon materials in preparing lithium-sulfur batteries. Background Art

[0002] With the rapid development of society, the demand for energy has increased dramatically. The excessive consumption of traditional fossil energy has led to increasingly serious problems such as environmental pollution and greenhouse effect, and due to the non-renewable nature of fossil energy, they cannot sustainably meet human needs. Therefore, the development and utilization of clean and renewable energy has always been a research hotspot in the field of new energy. As an efficient energy storage system, rechargeable batteries play a key role in the storage of clean and renewable electricity. Since their advent, lithium-ion batteries (LIBs) have been widely used in people's production and life. However, the energy density of lithium-ion batteries is limited by the specific capacity of the positive electrode material, making it difficult to achieve a significant increase.

[0003] Therefore, lithium-sulfur batteries have become a research hotspot for energy storage devices due to their abundant sulfur reserves, low price, high theoretical specific capacity (1675mAh / g) and theoretical energy density (2600Wh / kg). However, there are still some problems in the research process of lithium-sulfur batteries at this stage, which seriously limit their widespread application. For example, the shuttle effect of lithium polysulfide compounds (long-chain polysulfides diffuse from the cathode to the anode during battery operation and accumulate on the lithium sheet, reducing conductivity), low conductivity of sulfur, and volume expansion during discharge lead to poor cycle stability, poor rate performance, low Coulomb efficiency, and serious loss of active materials, thus restricting the commercialization of lithium-sulfur batteries.

[0004] In order to solve the above problems, researchers have proposed a variety of strategies, mainly including the functional design and synthesis of the positive electrode and the intermediate layer to adsorb and block the shuttle effect and promote the redox reaction of lithium polysulfides (LiPSs). In addition, it also includes the optimization of the electrolyte, such as the preparation of solid electrolytes to inhibit the dissolution and dispersion of LiPSs. At present, the use of multifunctional carbon materials to regulate the shuttle effect and promote the construction of modified diaphragms and high-sulfur host materials for LiPSs catalytic reactions has become the mainstream trend of research. However, the synthesis of these materials usually requires complex steps and long preparation time. Therefore, the large-scale synthesis of porous carbon materials using simple methods has become a hot topic of research. Multifunctional carbon materials prepared from biomass materials as energy storage materials have shown great and unique potential in the field of electrochemical energy storage. Unfortunately, most modified materials can only achieve one or two excellent properties, and it is difficult to have both high discharge specific capacity and the ability to effectively slow down the redox kinetics of LiPSs. These problems still limit the commercial development of lithium-sulfur batteries. Summary of the invention

[0005] The present invention aims to overcome the defects of the prior art and provide the use of aloe peel biocarbon material in the preparation of lithium-sulfur batteries.

[0006] Another object of the present invention is to provide a lithium-sulfur battery.

[0007] The technical solution of the present invention is as follows:

[0008] Use of aloe vera biocarbon material in preparing lithium-sulfur batteries, wherein the aloe vera biocarbon material is used as a raw material for preparing positive electrodes and diaphragms of lithium-sulfur batteries.

[0009] The raw material of the positive electrode includes KOH@AVP / S positive electrode material. The preparation method of the KOH@AVP / S positive electrode material includes: using aloe peel powder as raw material, sequentially performing 500°C high temperature annealing carbonization, KOH etching, 700°C high temperature annealing and pickling to obtain KOH@AVP, and then performing a sulfur melting reaction to obtain the KOH@AVP / S positive electrode material;

[0010] The raw materials of the diaphragm include Co@AVP diaphragm modified material. The preparation method of the Co@AVP diaphragm modified material includes: using aloe peel powder, urea and cobalt nitrate hexahydrate as raw materials, carrying out hydrothermal reaction, then adding pore-forming agents K2CO3 and CaCO3 for uniform ball milling, and then successively carrying out vacuum drying, high-temperature annealing at 500-700°C in an argon atmosphere and acid washing to obtain the Co@AVP diaphragm modified material.

[0011] In a preferred embodiment of the present invention, in the preparation method of the KOH@AVP / S positive electrode material: the 500°C high temperature annealing carbonization is: heating the aloe peel powder to 500°C at a heating rate of 5°C / min and keeping it warm for 3 hours; the KOH etching is: mixing the material obtained by the 500°C high temperature annealing carbonization with KOH evenly, stirring at 110°C for 12 hours to remove excess moisture, and then drying; the 700°C high temperature annealing is: heating the material obtained by KOH etching to 700°C at a heating rate of 2°C / min and keeping it warm for 1 hour, and performing KOH activation; the pickling is: pickling the material obtained by the 700°C high temperature annealing with hydrochloric acid, then washing it with deionized water, and then drying it to obtain KOH@AVP, and then performing a sulfur melting reaction to obtain the KOH@AVP / S positive electrode material.

[0012] Further preferably, the mass ratio of the material obtained by high temperature annealing and carbonization at 500° C. to KOH is 1:1-3.

[0013] In a preferred embodiment of the present invention, in the preparation method of the Co@AVP membrane modified material: the high-temperature annealing at 500-700°C in an argon atmosphere is as follows: the material obtained by vacuum drying is heated to 500°C at a heating rate of 5°C / min in an argon atmosphere, annealed for 1h30 min, then heated to 700°C at a heating rate of 2°C / min and kept warm for 2h, and then cooled naturally; the pickling is as follows: the material obtained by high-temperature annealing at 500-700°C in an argon atmosphere is pickled with hydrochloric acid, then washed thoroughly with deionized water, and then dried thoroughly.

[0014] Further preferably, the mass ratio of the aloe peel powder, urea and cobalt nitrate hexahydrate is 1:0.5-1:0.05-0.1; the temperature of the hydrothermal reaction is 80°C and the time is 12h; the mass ratio of the material obtained by the hydrothermal reaction to the pore-forming agents K2CO3 and CaCO3 is 1:0.5-1:0.5-1.

[0015] A lithium-sulfur battery comprises a positive electrode and a diaphragm, wherein the raw material of the positive electrode comprises a KOH@AVP / S positive electrode material, and the preparation method of the KOH@AVP / S positive electrode material comprises: using aloe peel powder as the raw material, sequentially performing high-temperature annealing carbonization at 500°C, KOH etching, high-temperature annealing at 700°C and pickling to obtain KOH@AVP, and then performing a sulfur melting reaction to obtain the KOH@AVP / S positive electrode material; the raw material of the diaphragm comprises a Co@AVP diaphragm modified material, and the preparation method of the Co@AVP diaphragm modified material comprises: using aloe peel powder, urea and cobalt nitrate hexahydrate as raw materials, performing a hydrothermal reaction, then adding pore-forming agents K2CO3 and CaCO3 for uniform ball milling, and then sequentially performing vacuum drying, high-temperature annealing at 500-700°C in an argon atmosphere and pickling to obtain the Co@AVP diaphragm modified material.

[0016] In a preferred embodiment of the present invention, in the preparation method of the KOH@AVP / S positive electrode material: the 500°C high temperature annealing and carbonization is: heating the aloe peel powder to 500°C at a heating rate of 5°C / min and keeping it warm for 3 hours; the KOH etching is: mixing the material obtained by the 500°C high temperature annealing and carbonization with KOH evenly, stirring at 110°C for 12 hours to remove excess moisture, and then drying; the 700°C high temperature annealing is: heating the material obtained by KOH etching to 700°C at a heating rate of 2°C / min and keeping it warm for 1 hour, and performing KOH activation; the pickling is: pickling the material obtained by the 700°C high temperature annealing with hydrochloric acid, then washing it with deionized water, and then drying it for 24 hours to obtain KOH@AVP, and then performing a sulfur melting reaction to obtain the KOH@AVP / S positive electrode material.

[0017] Further preferably, the mass ratio of the material obtained by high temperature annealing and carbonization at 500° C. to KOH is 1:1-3.

[0018] In a preferred embodiment of the present invention, in the preparation method of the Co@AVP membrane modified material: the high-temperature annealing at 500-700°C in an argon atmosphere is as follows: the material obtained by vacuum drying is heated to 500°C at a heating rate of 5°C / min in an argon atmosphere, annealed for 1h30 min, then heated to 700°C at a heating rate of 2°C / min and kept warm for 2h, and then cooled naturally; the pickling is as follows: the material obtained by high-temperature annealing at 500-700°C in an argon atmosphere is pickled with hydrochloric acid, then washed thoroughly with deionized water, and then dried thoroughly.

[0019] Further preferably, the mass ratio of the aloe peel powder, urea and cobalt nitrate hexahydrate is 1:0.5-1:0.05-0.1; the temperature of the hydrothermal reaction is 80°C and the time is 12h; the mass ratio of the material obtained by the hydrothermal reaction to the pore-forming agents K2CO3 and CaCO3 is 1:0.5-1:0.5-1.

[0020] The beneficial effects of the present invention are:

[0021] 1. The present invention uses aloe vera biomass carbon material as a precursor, obtains a positive electrode sulfur host KOH@AVP / S positive electrode material with a high specific surface area by KOH etching, and introduces Co metal nanoparticles by a simple hydrothermal reaction to prepare a Co@AVP diaphragm modified material that can be used to modify the diaphragm. These two materials are used in lithium-sulfur batteries at the same time and can play a synergistic role.

[0022] 2. The present invention applies aloe vera biomass carbon materials to the positive electrode material and diaphragm modification of lithium-sulfur batteries. This design not only provides sufficient space for the significant volume change of the sulfur positive electrode during the charge and discharge process, but also the Co metal nanoparticles loaded on the carbon material as active sites can effectively catalyze the conversion of polysulfides, inhibit the shuttle effect of polysulfides, and further accelerate the reaction kinetics. Therefore, the assembled lithium-sulfur battery exhibits excellent cycle stability and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 XRD patterns of all materials prepared in Example 1 and Example 2 of the present invention.

[0024] Figure 2 This is the SEM image of the KOH@AVP positive electrode material obtained in Example 1 of the present invention.

[0025] Figure 3 This is the SEM image of the Co@AVP membrane modified material obtained in Example 2 of the present invention.

[0026] Figure 4 This is a BET specific surface area diagram of the KOH@AVP positive electrode material prepared in Example 1 of the present invention and the Co@AVP membrane modified material prepared in Example 2.

[0027] Figure 5 A physical picture of a commercial membrane (left) and a lithium-sulfur battery membrane modified with the Co@AVP membrane-modifying material prepared in Example 1 of the present invention (right).

[0028] Figure 6 This is a rate performance test diagram of a 2025-type button-type lithium-sulfur battery assembled using the KOH@AVP / S positive electrode material prepared in Example 1 of the present invention and the Co@AVP / / PP prepared in Example 2.

[0029] Figure 7 This is a test chart of the cycle performance of a 2025-type button-type lithium-sulfur battery assembled by using the KOH@AVP / S positive electrode material prepared in Example 1 of the present invention and the Co@AVP / / PP prepared in Example 2. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is further illustrated and described below through specific implementation modes in combination with the accompanying drawings.

[0031] Example 1: Preparation of KOH@AVP / S cathode

[0032] (1) heating 15 g of aloe peel powder to 500° C. at a heating rate of 5° C. / min and high temperature annealing and carbonization for 3 h to obtain aloe peel biomass carbon material;

[0033] (2) taking out the aloe vera peel biomass carbon material, mixing it with KOH in a weight ratio of 1:3, adding deionized water, stirring at 110°C for etching reaction for 12 hours, then removing excess water and transferring it to a tube furnace, heating it to 700°C at a heating rate of 2°C / min and annealing it for 1 hour for KOH activation;

[0034] (3) The material obtained in step (2) was taken out and pickled with 1M hydrochloric acid for 12 h, then repeatedly rinsed with deionized water to remove excess KOH and other impurities, and then placed in a vacuum oven at 80° C. and dried for 12 h to obtain KOH@AVP;

[0035] (4) KOH@AVP and elemental sulfur were ground in a mortar at a mass ratio of 2:3 for more than 30 minutes to make them evenly mixed, and then placed in a sealed cillin bottle filled with argon and heated at 155°C for 12 hours to perform a sulfur melting reaction to obtain a KOH@AVP / S positive electrode material.

[0036] (5) KOH@AVP / S cathode material, Ketjen black and polyvinylidene fluoride (PVDF) were mixed in N-methylpyrrolidone (NMP) at a weight ratio of 7:2:1 to prepare an electrode slurry, which was then coated on aluminum foil by manual coating and then dried at 60°C to prepare a cathode electrode. The average sulfur loading of the manually cut cathode electrode sheet was 1.3 mg / cm 2 .

[0037] like Figure 1 As shown in FIG. 1 , the XRD pattern of KOH@AVP is shown in FIG. Figure 1 It can be seen that the KOH@AVP (101) peak, which is characteristic of the amorphous structure, is slightly weaker than that of AVP, indicating that the graphitization degree of KOH-L HP is slightly lower. Figure 2 The SEM image of KOH@AVP obtained in Example 1 is shown. Figure 2 It can be seen that KOH has an obvious etching effect on aloe peel carbon material, and it can be seen that it has many porous structures and Figure 4 The specific surface area of ​​KOH@AVP is 1982.1m 2 / g. This further proves that KOH@AVP provides a huge space for sulfur host before and after charge and discharge.

[0038] Example 2: Preparation of Co@AVP / / PP

[0039] (1) 2 g of aloe vera peel powder, 1 g of urea and 150 mg of cobalt nitrate hexahydrate were added to 25 mL of ethanol, stirred evenly at room temperature, and then subjected to hydrothermal reaction at 80° C. for 12 h to remove ethanol.

[0040] (2) The material obtained in step (1) and the pore-forming agents K2CO3 and CaCO3 are ball-milled in a mass ratio of 1:1:1.

[0041] (3) heating the material obtained in step (2) to 500° C. at a heating rate of 5° C. / min in an argon atmosphere, annealing for 1 h 30 min, then heating to 700° C. at a heating rate of 2° C. / min and maintaining for 2 h, and then cooling naturally;

[0042] (4) The material obtained in step (3) was acid-washed with 1M hydrochloric acid for 12 h, washed with a large amount of deionized water for 3 times, and then vacuum-dried at 80° C. for 24 h to obtain a Co@AVP membrane modified material;

[0043] (5) The Co@AVP membrane modified material was mixed with polyvinylidene fluoride (PVDF) in a mass ratio of 4:1, and uniformly dispersed in N,N-dimethylformamide (DMF) by ultrasonication for 2 h to obtain a slurry; the slurry was then vacuum filtered and assembled on the surface of a commercial diaphragm made of PP, and vacuum dried at 60°C for 12 h to obtain a Co@AVP / / PP lithium-sulfur battery diaphragm.

[0044] like Figure 1 The XRD pattern of the Co@AVP membrane modified material obtained in Example 2 is shown in FIG. Figure 1 It can be seen that the X-ray diffraction peaks of the membrane modified material Co@AVP sample correspond to the (111), (200), (220) crystal planes of metal Co at 44.2°, 51.5°, and 75.8° (PDF#15-0806). At the same time, it can be observed that there is a broad peak at 44.70°, corresponding to the graphitized carbon (101) plane, showing the characteristics of an amorphous structure. The Co@AVP (101) peak is slightly weaker than that of AVP, indicating that the degree of graphitization of Co@AVP is slightly lower, indicating that the Co metal nanoparticles are loaded on AVP and the material is successfully prepared. Figure 3 The SEM image of the Co@AVP membrane modified material obtained in Example 2 is shown. Figure 3 It can be clearly seen that Co nanoparticles are embedded inside the material, proving that Co nanoparticles are successfully loaded in the aloe peel carbon material. Figure 4 The specific surface area of ​​the Co@AVP membrane modified material is 2078.4 m 2 / g, which proves that it can provide sufficient space and expose more catalytic centers to capture and promote the redox of LiPSs. Figure 5 A commercial separator (left) and a lithium-sulfur battery separator modified with the Co@AVP separator-modified material prepared in Example 2 (right) are shown, indicating that the Co@AVP separator-modified material has been uniformly coated on the surface of the commercial separator.

[0045] Example 3: Preparation of a common sulfur cathode

[0046] The preparation process of this embodiment is to add sulfur powder, acetylene black, PVDF and other chemicals in a mass ratio of 6:3:1 into an agate pot, then add an appropriate amount of N-methylpyrrolidone (NMP), and stir for 3 hours with a ball mill at a speed of 250 rpm to obtain a slurry. The obtained slurry is coated on aluminum foil and dried in a vacuum oven at 60°C for 12 hours to obtain a sulfur content of about 1.3 mg / cm -2 Ordinary sulfur cathode.

[0047] Example 4: Assembly of lithium-sulfur battery

[0048] The preparation process of this embodiment is to stack and assemble the KOH@AVP / S cathode material and Co@AVP / / PP modified diaphragm, lithium-sulfur commercial battery electrolyte, metal lithium sheet, gasket, shrapnel, and battery positive and negative electrode shells prepared in Example 1, and then seal them to assemble into 2025-type button batteries. And use ordinary sulfur cathode and unmodified diaphragm, lithium-sulfur commercial battery electrolyte, metal lithium sheet, gasket, shrapnel, and battery positive and negative electrode shells to stack and assemble, and then seal them to assemble into 2025-type button batteries as comparative blank batteries.

[0049] like Figure 6 As shown in FIG. 4 , it is a rate performance test diagram of a 2025-type button-type lithium-sulfur battery assembled by the KOH@AVP / S positive electrode material and Co@AVP / / PP obtained in Example 4. Figure 6 It can be clearly seen that the rate performance of the lithium-sulfur battery assembled by the linkage of KOH@AVP / S cathode material and Co@AVP / / PP is significantly higher than that of the blank battery, and the lithium-sulfur battery assembled by the linkage of KOH@AVP / S cathode material and Co@AVP / / PP can maintain a high capacity of 891.58m mAh / g at a high rate of 4C, proving that the battery can maintain a small polarization at a high rate. Figure 7 The figure shows the cycle performance test of the 2025-type button-type lithium-sulfur battery assembled by the KOH@AVP / S positive electrode material and Co@AVP / / PP obtained in Example 4. Figure 7 It can be seen that the lithium-sulfur battery still has a discharge capacity of 590.84 mAh / g after 800 cycles at 1C, which is significantly higher than the discharge capacity of the blank battery (96.04 mA h / g), achieving high energy density. It proves that the long cycle experiment of the battery shows good cycle stability.

[0050] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.

Claims

1. The use of aloe peel biocarbon material in the preparation of lithium-sulfur batteries, characterized in that: The aloe vera peel biocarbon material is used as a raw material for preparing the positive electrode and the diaphragm of the lithium-sulfur battery. The raw material of the positive electrode includes KOH@AVP / S positive electrode material. The preparation method of the KOH@AVP / S positive electrode material includes: using aloe peel powder as raw material, sequentially performing 500°C high temperature annealing carbonization, KOH etching, 700°C high temperature annealing and pickling to obtain KOH@AVP, and then performing a sulfur melting reaction to obtain the KOH@AVP / S positive electrode material; The raw materials of the diaphragm include Co@AVP diaphragm modified material. The preparation method of the Co@AVP diaphragm modified material includes: using aloe peel powder, urea and cobalt nitrate hexahydrate as raw materials, carrying out hydrothermal reaction, then adding pore-forming agents K2CO3 and CaCO3 for uniform ball milling, and then successively carrying out vacuum drying, high-temperature annealing at 500-700°C in an argon atmosphere and acid washing to obtain the Co@AVP diaphragm modified material.

2. The use according to claim 1, characterized in that: In the preparation method of the KOH@AVP / S positive electrode material, the 500°C high-temperature annealing and carbonization is as follows: the aloe peel powder is heated to 500°C at a heating rate of 5°C / min and kept warm for 3 hours; the KOH etching is as follows: the material obtained by the 500°C high-temperature annealing and carbonization is evenly mixed with KOH, stirred at 110°C for 12 hours to remove excess moisture, and then dried; the 700°C high-temperature annealing is as follows: the material obtained by the KOH etching is heated to 700°C at a heating rate of 2°C / min and kept warm for 1 hour to perform KOH activation; the pickling is as follows: the material obtained by the 700°C high-temperature annealing is pickled with hydrochloric acid, then fully washed with deionized water, and then fully dried to obtain KOH@AVP, and then subjected to sulfur melting reaction to obtain KOH@AVP / S positive electrode material.

3. The use according to claim 2, characterized in that: The mass ratio of the material obtained by annealing and carbonization at 500° C. to KOH is 1:1-3.

4. The use according to claim 1, characterized in that: In the preparation method of the Co@AVP membrane modified material: the high-temperature annealing in an argon atmosphere at 500-700°C is as follows: the material obtained by vacuum drying is heated to 500°C at a heating rate of 5°C / min in an argon atmosphere, annealed for 1h30min, then heated to 700°C at a heating rate of 2°C / min and kept warm for 2h, and then cooled naturally; the pickling is as follows: the material obtained by high-temperature annealing in an argon atmosphere at 500-700°C is pickled with hydrochloric acid, then fully washed with deionized water, and then fully dried.

5. The use according to claim 4, characterized in that: The mass ratio of the aloe peel powder, urea and cobalt nitrate hexahydrate is 1:0.5-1:0.05-0.1; the temperature of the hydrothermal reaction is 80°C and the time is 12h; the mass ratio of the material obtained by the hydrothermal reaction to the pore-forming agents K2CO3 and CaCO3 is 1:0.5-1:0.5-1.

6. A lithium-sulfur battery having a positive electrode and a separator, characterized in that: The raw material of the positive electrode includes KOH@AVP / S positive electrode material, and the preparation method of the KOH@AVP / S positive electrode material includes: using aloe peel powder as raw material, sequentially performing high-temperature annealing carbonization at 500°C, KOH etching, high-temperature annealing at 700°C and pickling to obtain KOH@AVP, and then performing a sulfur melting reaction to obtain the KOH@AVP / S positive electrode material; the raw material of the diaphragm includes Co@AVP diaphragm modified material, and the preparation method of the Co@AVP diaphragm modified material includes: using aloe peel powder, urea and cobalt nitrate hexahydrate as raw materials, performing a hydrothermal reaction, then adding pore-forming agents K2CO3 and CaCO3 for uniform ball milling, and then sequentially performing vacuum drying, high-temperature annealing at 500-700°C in an argon atmosphere and pickling to obtain the Co@AVP diaphragm modified material.

7. A lithium-sulfur battery as claimed in claim 6, characterized in that: In the preparation method of the KOH@AVP / S positive electrode material, the 500°C high-temperature annealing and carbonization is as follows: the aloe peel powder is heated to 500°C at a heating rate of 5°C / min and kept warm for 3 hours; the KOH etching is as follows: the material obtained by the 500°C high-temperature annealing and carbonization is evenly mixed with KOH, stirred at 110°C for 12 hours to remove excess moisture, and then dried; the 700°C high-temperature annealing is as follows: the material obtained by the KOH etching is heated to 700°C at a heating rate of 2°C / min and kept warm for 1 hour to perform KOH activation; the pickling is as follows: the material obtained by the 700°C high-temperature annealing is pickled with hydrochloric acid, then fully washed with deionized water, and then fully dried to obtain KOH@AVP, and then subjected to sulfur melting reaction to obtain KOH@AVP / S positive electrode material.

8. A lithium-sulfur battery as claimed in claim 7, characterized in that: The mass ratio of the material obtained by annealing and carbonization at 500° C. to KOH is 1:1-3.

9. A lithium-sulfur battery as claimed in claim 6, characterized in that: In the preparation method of the Co@AVP membrane modified material: the high-temperature annealing in an argon atmosphere at 500-700°C is as follows: the material obtained by vacuum drying is heated to 500°C at a heating rate of 5°C / min in an argon atmosphere, annealed for 1h30min, then heated to 700°C at a heating rate of 2°C / min and kept warm for 2h, and then cooled naturally; the pickling is as follows: the material obtained by high-temperature annealing in an argon atmosphere at 500-700°C is pickled with hydrochloric acid, then fully washed with deionized water, and then fully dried.

10. A lithium-sulfur battery as claimed in claim 9, characterized in that: The mass ratio of the aloe peel powder, urea and cobalt nitrate hexahydrate is 1:0.5-1:0.05-0.1; the temperature of the hydrothermal reaction is 80°C and the time is 12h; the mass ratio of the material obtained by the hydrothermal reaction to the pore-forming agents K2CO3 and CaCO3 is 1:0.5-1:0.5-1.

Citation Information

Patent Citations

  • Cobalt oxide-aloe derived porous layer carbon composite electrode material and synthesis method and application thereof

    CN111261417A

  • Tellurium Nanostructures with Antimicrobial and Anticancer Properties Synthesized by Aloe Vera-Mediated Green Chemistry

    US20220071919A1

  • KR20240156687A